Public Space and Economic Behavior: Study of Social Activities in the Car Free Day Boulevard Area, Makasar City - Misbawati, Misbawati; Ahmadin, Ahmadin (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2025)
When social and cultural changes move so quickly due to the influence of scientific and technological developments, public spaces appear in various forms. One form of public space is the Car Free Day area which is often found in cities throughout the world, including in Indonesia. This article examines one of the Car Free Day areas in Makassar City, South Sulawesi Province, which is located on Jalan Boulevard with an economic behavior analysis unit. The research results show that behind the community activities that use this area as a means of sports, a place to relax and for social interaction, there is also economic behavior that is interesting to study. This area is certainly not the only place that can be used as a place for interpersonal interaction and is not the only place that offers various kinds of products for sale, but it can also be found in many places.